2022
DOI: 10.3389/fneur.2022.811490
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Transformation of Visual Snow Syndrome From Episodic to Chronic Associated With Acute Cerebellar Infarct

Abstract: Visual snow syndrome is a novel neurological condition characterized by a panfield visual disturbance associated with several additional symptoms. Although it is usually a continuous and primary disorder, cases of intermittent visual snow have been described in the literature, as well as rare secondary forms. This report is the first description of a case of intermittent visual snow syndrome, which transformed into a persistent form following a posterior circulation stroke due to vertebral artery dissection. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
2
0
2
Order By: Relevance
“…The changes in the cerebellum might represent a broader network-like disorder, but when corrected for age, sex, handedness, and duration of disease, were not significant [ 19 ]. Another argument for cerebellar participation in VSS pathophysiology is shown in a case report describing a transformation from episodic to chronic VSS after infarction of the right superior cerebellar artery territory [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The changes in the cerebellum might represent a broader network-like disorder, but when corrected for age, sex, handedness, and duration of disease, were not significant [ 19 ]. Another argument for cerebellar participation in VSS pathophysiology is shown in a case report describing a transformation from episodic to chronic VSS after infarction of the right superior cerebellar artery territory [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prospective studies have shown that VSS symptoms tend to remain stable over time and are not expected to cease [ 10 , 11 ]. The visual snow itself can, however, manifest episodically, and either remain as an ictal disorder or later evolve into the classic form of VSS [ 12 14 ]. In these cases visual snow should carefully be distinguished from visual aura or other visual phenomena associated with migraine [ 15 ].…”
Section: What Is Visual Snow?mentioning
confidence: 99%
“…F. Puledda и соавт. [2] опубликовали описание случая трансформации эпизодического ВС в постоянный у 44-летнего мужчины после развития инсульта в вертебробазилярном бассейне на фоне диссекции правой позвоночной артерии. И наоборот, имеются данные, согласно которым в течение недели после геморрагического инсульта в области левого таламуса последовало кратковременное разрешение СВС у 25-летней женщины [21].…”
unclassified
“…Случай СВС на фоне ишемического инсульта в гемисфере мозжечка, описанный F. Puledda и соавт. [2], указывает на вовлеченность мозжечка в патофизиологию СВС. Как известно, задняя часть мозжечка играет ключевую роль не только в двигательных функциях, но также в сенсомоторной и когнитивной интеграции.…”
unclassified